2004
DOI: 10.1097/00126097-200408000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antihypertensive activity of telmisartan compared with valsartan

Abstract: Due to its longer half-life, telmisartan offers more sustained BP control, especially at the end of the dosing period and provides sustained efficacy in poorly compliant patients in the event of a missed dose with a statistical superiority compared with valsartan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 15 publications
0
52
0
5
Order By: Relevance
“…Not surprisingly, both fixed-dose combination agents lowered BP to a much greater extent than placebo. The findings between the active treatment groups were predictable, in part, considering the pharmacokinetic profile of telmisartan, which is characterized by a longer half-life than valsartan [9,12] and previous pharmacodynamic studies using ambulatory BP monitoring that showed greater BP reductions on telmisartan compared with valsartan without the diuretic component [15][16][17]. Thus, the current study confirms what has already been demonstrated comprehensively regarding the combination therapies for the angiotensin II receptor blockers that utilize a higher dose of hydrochlorothiazide (25 mg) [13], an option that has been shown to be increasingly useful in clinical hypertension management [3,12].…”
Section: Principal Findingsmentioning
confidence: 63%
See 1 more Smart Citation
“…Not surprisingly, both fixed-dose combination agents lowered BP to a much greater extent than placebo. The findings between the active treatment groups were predictable, in part, considering the pharmacokinetic profile of telmisartan, which is characterized by a longer half-life than valsartan [9,12] and previous pharmacodynamic studies using ambulatory BP monitoring that showed greater BP reductions on telmisartan compared with valsartan without the diuretic component [15][16][17]. Thus, the current study confirms what has already been demonstrated comprehensively regarding the combination therapies for the angiotensin II receptor blockers that utilize a higher dose of hydrochlorothiazide (25 mg) [13], an option that has been shown to be increasingly useful in clinical hypertension management [3,12].…”
Section: Principal Findingsmentioning
confidence: 63%
“…The primary findings demonstrated that telmisartan-HCT 80/25 lowered both the systolic and diastolic BP to a greater extent than valsartan-HCT MedDRA preferred term [17]. BP, blood pressure; HCT, hydrochlorothiazide.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Amlodipine and telmisartan have long half-lives and, therefore, long duration of action. Indeed, telmisartan provides longlasting and consistent BP control over a 24-h period compared with other renin-angiotensin system inhibitors [9,[27][28][29], and this is the case also for amlodipine when compared with other calcium channel blockers [30,31]. Visitto-visit variability in SBP and maximum SBP are strong predictors of stroke, and in patients with treated hypertension, increased 24-h residual variability in SBP is associated with a high risk of vascular events [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ABPM data from the individual clinical studies available and meta-analysis of these data provide a clear demonstration of the 24-hour BP control provided by telmisartan and offer demonstration that the degree of BP reduction that is still evident at the end of the dosing interval is significantly greater than the corresponding BP reduction offered by other ARBs, such as losartan and valsartan [48][49][50][51]. In a study comparing telmisartan with valsartan, this was the case also in the event of a missed dose [52]. SIs computed from SBP and DBP ABPM measurements of fixed-dose studies of telmisartan demonstrate that telmisartan 80 mg has the highest SI for both SBP and DBP compared with losartan, valsartan, and amlodipine (Table 1) [53], thus further supporting its ability to provide a smooth and sustained antihypertensive activity throughout the interval between once-daily doses.…”
Section: Abpm Evaluation Of Antihypertensive Agents In Clinical Trialsmentioning
confidence: 99%